Music induced emotion using wavelet packet decomposition—An EEG study. (April 2018) - Balasubramanian, Geethanjali; Kanagasabai, Adalarasu; Mohan, Jagannath; Seshadri, N.P. Guhan
Highlights: Analyzed the dynamic emotional responses of the participants to self-selected music using EEG measures. Implementeda multi-resolution analysis algorithm using wavelet packet decomposition for music induced emotion. Observed increase in theta and beta component energies while listening to dislike music. Participants' perceived emotion corroborates with induced emotion for self-selected music. Abstract: Music has the potential to invoke strong emotions, both positive and negative, wherein positive emotions can augment well-being. The objective of this study was to analyze the dynamic emotional responses of the participants to self-selected music using Electroencephalography (EEG). The frequency localization with respect to time for the given stimulus (liked and disliked music) in various EEG bands was established by implementing a multi-resolution analysis algorithm using Wavelet Packet Decomposition (WPD).Ten healthy adults with an average age of 20 years (without any formal training in music) participated in this study. The perceived emotion of the participants was assessed using Self-Assessment Manikin (SAM) scale and brain activity, while they were listening to music, was recorded using EEG. A high frontal asymmetry index score was noted at mid-frontal (F3 and F4) and lateral frontal (F7 and F8) electrode locations indicating positive emotion. The result suggests that playing the disliked music elicits neither negative emotion nor positive emotion as the changes were noted only at lateral frontal (F4 and F3). Apart from these, there was an increase in the theta band energy of the frontal midline only for liked music and increased beta component energy was observed only at frontal electrode locations while listening to disliked music. The participants' perceived emotion (valence/arousal) matched with induced emotion for liked music whereas for disliked music only the arousal component was similar.